2017
DOI: 10.1001/jama.2017.5706
|View full text |Cite
|
Sign up to set email alerts
|

Management of Depression in Older Adults

Abstract: Major depression in older adults is common and can be effectively treated with antidepressants and electroconvulsive therapy. Psychological therapies and exercise may also be effective for mild-moderate depression, for patients who prefer nonpharmacological treatment, or for patients who are too frail for drug treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
447
4
36

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 688 publications
(495 citation statements)
references
References 85 publications
8
447
4
36
Order By: Relevance
“…107,108 Antidepressant medications also carry significant side effects, especially in elderly patients already under a burden of iatrogenic polypharmacy. 109 Our survey respondents reported marked improvements in symptoms of anxiety and depression after starting a low-carbohydrate diet. These findings support low-carbohydrate nutrition as an alternative therapeutic approach for some mental health conditions and warrant continued research.…”
mentioning
confidence: 78%
“…107,108 Antidepressant medications also carry significant side effects, especially in elderly patients already under a burden of iatrogenic polypharmacy. 109 Our survey respondents reported marked improvements in symptoms of anxiety and depression after starting a low-carbohydrate diet. These findings support low-carbohydrate nutrition as an alternative therapeutic approach for some mental health conditions and warrant continued research.…”
mentioning
confidence: 78%
“…8,9 Recent surveys have indicated that around 8% of community-dwelling Australians aged over 60 years 10 and 11% of over 70 years US population experience clinically significant depression. 17,18 Although rates of depression treatment are increasing, 19 many people still do not have adequate control of depressive symptoms. Regardless of cutoff's for diagnosis of major depression, the presence of minor or subthreshold symptoms was shown to severely impact outcomes in older individuals.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 A large representative German sample of people aged 53 to 80 years showed a U-shaped association between age category and depression prevalence. 9 Various factors account for the difficulties surrounding diagnosis of depression in older adults such as somatic comorbidities, a tendency that older persons are more likely to seek care in the primary care sector rather than in specialized mental health care institutions, 10 and a shortage of mental health care providers. According to the most recent German guideline, both pharmacotherapy and psychotherapy are considered as evidence-based treatment options for patients with depression.…”
Section: Introductionmentioning
confidence: 99%